PHARYNGEAL SWALLOWING MECHANICS SECONDARY TO HEMISPHERIC STROKE - May, Nelson H (J Stroke Cerebrovasc Dis, 2016)
GOALS: Computational Analysis of Swallowing Mechanics is a method that utilizes multivariate shape change analysis to uncover covariant elements of pharyngeal swallowing mechanics associated with impairment using videofluoroscopic swallowing studies. The goals of this preliminary study were to (1) characterize swallowing mechanics underlying stroke related dysphagia, (2) decipher the impact of left and right hemispheric stroke on pharyngeal swallowing mechanics, and (3) determine pharyngeal swallowing mechanics associated with penetration-aspiration status. MATERIALS AND METHODS: Videofluoroscopic swallowing studies of 18 dysphagic patients with hemispheric infarcts and age and gender matched controls were selected from well-controlled data sets. Patient data including laterality, and penetration-aspiration status was collected. Coordinates mapping muscle group action during swallowing were collected from videos. Multivariate morphometric analyses of coordinates associated with stroke, affected hemisphere, and penetration-aspiration status were performed. FINDINGS: Pharyngeal swallowing mechanics differed significantly in the following comparisons: stroke vs. controls (D=2.19, p<.0001); right hemispheric stroke vs. controls (D=3.64, p<.0001); left hemispheric stroke vs. controls (D=2.06, p<.0001); right hemispheric stroke vs. left hemispheric stroke (D=2.89, p<.0001); and penetration-aspiration vs. within normal limits (D=2.25, p<.0001). Differences in pharyngeal swallowing mechanics associated with each comparison were visualized using eigenvectors. CONCLUSION: While current literature focuses on timing changes in stroke-related dysphagia, this data suggests that mechanical changes are also functionally important. Pharyngeal swallowing mechanics differed by affected hemisphere and penetration-aspiration status. Computational Analysis of Swallowing Mechanics can be used to identify patient specific swallowing impairment associated with stroke injury that could help guide rehabilitation strategies to improve swallowing outcomes.